ENHANCING STUDENTS’ CRITICAL THINKING WITH PROJECT-BASED LEARNING IN ELEMENTARY SCHOOL - Sri Intan; Muhamad Ahyar Rasidi; Adamu Abubakar Muhammad (MEDIA DAN STRATEGI PEMBELAJARAN, 2025)
This study aims to improve students' critical thinking skills by implementing the project-based learning model in the science subject in class IV SDN 47 Ampenan. The type of research used is classroom action research (CAR), which consists of II cycles, each consisting of 2 meetings, which goes through four stages: planning, implementation, observation, and reflection. The research methods used are observation, testing, and documentation. The data analysis uses a quantitative approach to calculate the average value and qualitative to analyze the results of observations of teacher and student activities during the learning process. The results of this study indicate that implementing the project-based learning Model can improve students' critical thinking skills in the subject of science in class IV SDN 47 Ampenan. This is evidenced by the results of the critical thinking ability evaluation test, observations of teacher activities, and the results of observations of student activities. The increase in students' critical thinking skills from 69.25% (cycle I) to 90.2% (cycle II) is 20.95%. Meanwhile, the results of teacher activity observations increased from cycle I to cycle II by 86.67% to 100%, or an increase of 13.33%. Likewise, the results of student activity observations increased from cycle I to cycle II by 78.3% to 93.3%, an increase of 15%.